BRICOLAGE AS INNOVATION: OPENING THE BLACK BOX OF DRIP IRRIGATION SYSTEMS1. (7th May 2014) - Benouniche, Maya; Zwarteveen, Margreet; Kuper, Marcel
ABSTRACT In Morocco, many farmers enthusiastically use drip irrigation. However, few drip irrigation systems conform to engineering standards. In a process they refer to as bricolage, farmers modify and adapt standard designs, thus creating their own technical standards. We document three instances of bricolage and show that it is a useful term to explain irrigation innovation processes. Through bricolage farmers adapt and modify the system to their needs, but also enter a process of gradual learning about what drip irrigation is and what it can achieve. Bricolage has led to the multiplication and diversification of drip systems, with different categories of users co‐designing the nature and direction of change it provokes. Through bricolage, local actors effectively share responsibilities of the design process with engineers. The paper concludes that the fact that drip irrigation lends itself to bricolage helps explain its success as an innovation. Copyright © 2014 John Wiley & Sons, Ltd.